2021
DOI: 10.29045/14784726.2021.09.6.2.66
|View full text |Cite
|
Sign up to set email alerts
|

Frequent callers to UK ambulance services in the COVID-19 pandemic: managing mental health, social isolation and loneliness

Abstract: Objectives: Patients who frequently call ambulance services are a vulnerable yet heterogeneous population with unmet multiple and complex physical health, mental health and/or social care needs. In this article, we report the challenges that the COVID-19 pandemic has introduced for ambulance services across the UK when managing frequent callers, and reflect on how existing systems and practices are adapting to support changing patient needs.Methods: Data reported in this article comprise reflections from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…It should be noted that the data were based on call disposition only, and the accuracy of these dispositions is unknown. The evidence base suggests that poor mental health is a significant contributing factor in frequent use of healthcare services ( Soril et al, 2016 ), and therefore the 8.4% of incidents identified as being psychiatric / suicide attempt, which is the only disposition related solely to mental health, is likely to be a large underestimate of the extent that poor mental health is contributing to frequent use, or the complex interaction that exists between the triad of physical health, mental health and social conditions ( Kuek et al, 2019 ; Scott et al, 2021 ; Søvsø et al, 2019 ; Urbanoski et al, 2018 ). Similarly, none of the dispositions are able to identify social conditions or wider determinants of health which are known to contribute to frequent use ( Agarwal et al, 2019 ; Kuek et al, 2019 ; Mahmuda et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that the data were based on call disposition only, and the accuracy of these dispositions is unknown. The evidence base suggests that poor mental health is a significant contributing factor in frequent use of healthcare services ( Soril et al, 2016 ), and therefore the 8.4% of incidents identified as being psychiatric / suicide attempt, which is the only disposition related solely to mental health, is likely to be a large underestimate of the extent that poor mental health is contributing to frequent use, or the complex interaction that exists between the triad of physical health, mental health and social conditions ( Kuek et al, 2019 ; Scott et al, 2021 ; Søvsø et al, 2019 ; Urbanoski et al, 2018 ). Similarly, none of the dispositions are able to identify social conditions or wider determinants of health which are known to contribute to frequent use ( Agarwal et al, 2019 ; Kuek et al, 2019 ; Mahmuda et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other countries where similar issues have been identified include -but are not limited to -Denmark (Søvsø et al, 2019) Netherlands (Maruster et al, 2021) and Singapore (Kuek et al, 2019). Furthermore, mental health, specifically anxiety, and social isolation were identified by emergency medical service providers in the United Kingdom to have been contributing factors in changes to frequent use during the early stages of the COVID-19 pandemic (Scott et al, 2021). Systematic reviews of frequent ambulance service use identified that there was no single standard definition internationally for adult (Scott et al, 2014b) or paediatric patients (Scott et al, 2022) and a recent commentary on the topic by Brown et al (2019) called for standardised definitions of frequent use of ambulance services.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation